Evaluasi Karakteristik Fisik, Komposisi Kimia dan Kualitas Mikrobia Karkas Broiler Beku yang Beredar di Pasar Tradisional Kabupaten Halmahera Utara, Maluku Utara (Evaluation of Physical Characteristics, Chemical Composition and Microbial Quality of Frozen - Dellen Naomi Matulessy; Edi Suryanto; Rusman (Rusman) (Buletin Peternakan, 2010)
The experiment was conducted to evaluate the quality of frozen broiler carcass sold in traditional markets of North Halmahera. Samples were taken from three traditional markets that selling frozen broilers and five sellers for each market were chosen. Three carcasses were taken from each trader replications. Macroscopic observation was done by seven panelists to asses 14 carcasses from each seller. Parameters observed were macroscopic characteristis of carcasses i.e. conformation, fleshing, fat cover, wholeness, discoloration, defeathering, color, and aroma of carcass. Physical characteristis determined were pH, cooking loss, water-holding capacity, and tenderness. Chemical composition included water, fat, and protein contents, and microbial quality consisted of total microbial, Coliform and Escherichia coli bacteria. Macroscopic characteristic data were assessed using descriptive analysis based on National Standard, whereas physical quality, chemical and microbial quality data were analyzed using analysis of variancecompletely randomized design. The differences between means, were tested using Duncan’s new Multiple Range Test. The results showed that the average macroscopic properties of conformation, fleshing, fat covering, wholeness,discoloration, defeathering and the colour of frozen broiler carcasses with score I, were 40.41, 38.16, 50.41, 49.80, 49.59, and 50.82% respectively. Quality factor of the aroma/odor of a carcass with score II was 63.47%. The data ofphysical quality of broiler meat were as follow: pH 6.16, cooking loss 21.72%, water-holding capacity 23.01%, and tenderness 2.81 kg/cm2. The chemical composition of broiler meat were moisture 71.93%, lipid 2.50% and protein20.11%. Data of microbial quality of broiler carcass were total plate count 7.1x105 cfu/g, and E.coli 0.8x101 cfu/g, there was not any significant differences between the seller, however there was significant differences among the selleron the number of coliform (P<0.05). The conclusions of the experiment were that broiler carcasses sold in the traditional market in North Halmahera in respect of their physical characteristics and their chemical composition have not altered, whereas the microbial quality such as total plate count and E.coli number was still below threshold. Furthermore, coliform population was also below the maximum number allowed.(Key words: Traditional market, Broilers frozen, Physical characteristics, Chemical composition, Microbial quality)